IMPLEMENTASI KEBIJAKAN KABUPATEN LAYAK ANAK BIDANG KESEJAHTERAAN SOSIAL DI KABUPATEN KARAWANG: Implementasi Kebijakan Kabupaten Layak Anak Bidang Kesejahteraan Sosial di Kabupaten Karawang - Pratiwi, Amalia; Sutarsih, Popon; Indrakentjana, Bambang (Pekerjaan Sosial, 2023)
The aim of this research is to analyze the implementation of the Child Friendly Regency Policy (KLA) in Karawang Regency. For analysis purposes, George C. Edward III’s (1980) theory is used (which includes four aspects, namely aspects of communication, resources, disposition and bureaucratic structure. This research uses a qualitative descriptive approach. This research selects informants purposively because they are people who are directly involved in the implementation of KLA in Karawang Regency or have information about it. The informants for this research came from personnel from the Social Service, Child Welfare Institutions (LKSA), and beneficiaries. The data collection methods used were in-depth interviews, observation and study documentation. The research results show that the four aspects that are of concern in the research, namely communication, resources, disposition and bureaucratic structure - have not been implemented optimally. This affects the achievement of the KLA implementation goal, namely that Karawang Regency is free of children’s social problems. Conclusions from This research shows that the implementation of the Child Friendly Regency policy in Karawang Regency has not been implemented optimally. Based on this research, it is recommended that socialization, training/coaching of officers, mapping of the bureaucratic structure by the Regional Government of Karawang Regency is necessary in order to optimize the implementation of the KLA. Keywords: Social work, policy implementation, child-friendly districts, child welfare.